Access to pulmonary rehabilitation: perspectives of patients, loved ones and healthcare professionals - Marques, A. (2021)
Introduction: Improving access to pulmonary rehabilitation (PR) is an international priority, but due to several constraints, healthcare professionals are often faced with the challenge of having to prioritise patients. Evidence from quantitative research suggests that symptoms, functional and health status and not lung function should guide referrals to pulmonary rehabilitation (PR). Whether these criteria are corroborated by the opinions of different stakeholders remains unknown. This qualitative study explored criteria, barriers and facilitators to access PR from the perspectives of people with chronic respiratory disease (CRD), loved ones and healthcare professionals. Methods: An exploratory, cross-sectional qualitative study was carried out. Focus groups were conducted separately with people with CRD, loved ones and healthcare professionals; transcribed verbatim and analysed thematically. All participants had previous experience with PR. Results: Seven focus groups were conducted: four with people with CRD (24 with chronic obstructive pulmonary disease and 5 with interstitial lung disease, 75.9% male, 68.4 ± 7.5 years); one with loved ones (n = 5, 100% female, 66.6 ± 7.7 years) and two with healthcare professionals (n = 16, 25% male, 38 ± 9.2 years). Perspectives among stakeholders were mostly consensual and organised in three themes: all people with CRD should have access to PR and as early as possible “Universal access”; if prioritisation is needed then priority should be given to those motivated, with high symptom burden and impaired functional status “Priority to those struggling and motivated”; and education about PR and continuity and communication between care settings and professionals are lacking to improve access to PR “Communication, dissemination and organisation as main keys”. Conclusions: Our findings corroborate previous evidence and provide new and complementary in-depth understanding to design interventions to improve access to PR in line with the perspectives of different stakeholders.